Preoperative Hepatic and Regional Arterial Chemotherapy in Patients Who Underwent Curative Colorectal Cancer Resection: A Prospective, Multi-center, Randomized Controlled Trial. Issue 6 (June 2021) - Zhu, Dexiang; Xia, Jianguo; Gu, Yan; Lin, Jianjiang; Ding, Kefeng; Zhou, Bo; Liang, Fei; Liu, Tianshu; Qin, Chunzhi; Wei, Ye; Ren, Li; Zhong, Yunshi; et al.
Abstract : Objective: To evaluate the effects of the addition of preoperative hepatic and regional arterial chemotherapy (PHRAC) on prognosis of stage II and III colorectal cancer (CRC) in a multicenter setting. Summary of Background Data: Our previous single-center pilot trial suggested that PHRAC in combination with surgical resection could reduce the occurrence of liver metastasis (LM) and improve survival in CRC patients. Methods: A prospective multi-center randomized controlled trial was conducted from December 2008 to December 2012 at 5 hospitals in China. Eligible patients with clinical stage II or III CRC who underwent curative resection were randomized to receive PHRAC plus adjuvant therapy (PHRAC arm) or adjuvant therapy alone (control arm). The primary endpoint was DFS. Secondary endpoints were cumulative LM rates, overall survival (OS), and safety (NCT00643877). Results: A total of 688 patients from 5 centers in China were randomly assigned (1:1) to each arm. The five-year DFS rate was 77% in the PHRAC arm and 65% in the control arm (HR = 0.61, 95% CI 0.46–0.81; P = 0.001). The 5-year LM rates were 7% and 16% in the PHRAC and control arms, respectively (HR = 0.37, 95% CI 0.22–0.63; P < 0.001). The 5-year OS rate was 84% in the PHRAC arm and 76% in the control arm (HR = 0.61, 95% CI 0.43–0.86; P = 0.005). There were no significant differences regarding treatment related morbidity or mortality between the two arms. Conclusions: The addition of PHRAC could improve DFS in patients with stage II and III CRC. It reduced the incidence of LM and improved OS without compromising patient safety. Trial Registration: ClinicalTrials.gov identifier: NCT00643877. Abstract : Supplemental Digital Content is available in the text